THE ADAPTATION OF THE GENERAL ASSESSMENT METHODS OF EFFICIENCY OF LEGAL NORMS TO THE NECESSITY OF DETERMINING THE EFFECTIVENESS OF THE NORMS OF THE LABOR LAW OF UKRAINE - Купіна, Людмила Францівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The aim: the article deals with analysis of the major provisions which are characterized the efficiency of legal norms. The methods of the research: the main attention is paid to research the method of efficiency of legal norms. Results: furthermore, the author considered the facilities of applying various methodological approaches in making an assessment of labor law. Discussion: when evaluating the effectiveness of the rules of labor law, as well as the norms of another branch of law, objective factors should be established that positively or negatively influence the final results of law enforcement activities.